2021
DOI: 10.3724/sp.j.1089.2021.18640
|View full text |Cite
|
Sign up to set email alerts
|

Human Action Recognition Method Based on Multi-Attention Mechanism and Spatiotemporal Graph Convolution Networks

Abstract: Human action recognition has become a challenging task in computer vision because it is difficult to combine spatiotemporal information. A multi-attention spatiotemporal graph convolution network is proposed.The core idea is to construct a connected graph according to the time series information and natural connection of human skeleton, and use the spatiotemporal graph convolution network with multi-attention mechanism to automatically learn spatial and temporal features and optimize the connected graph to rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It has been found that circular shapes contribute to higher cognitive efficiency than other contours; shapes with topological differences are more visually shapes with topological consistency 1 . The purpose of this experiment was to verify the existence of an influential role of different topologies of icons on visual search performance.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…It has been found that circular shapes contribute to higher cognitive efficiency than other contours; shapes with topological differences are more visually shapes with topological consistency 1 . The purpose of this experiment was to verify the existence of an influential role of different topologies of icons on visual search performance.…”
Section: Methodsmentioning
confidence: 95%
“…It has been found that circular shapes contribute to higher cognitive efficiency than other contours; shapes with topological differences are more visually shapes with topological consistency. 1 The purpose of this experiment was to verify the existence of an influential role of different topologies of icons on visual search performance. Therefore, this paper taking data icon shapes of nuclear power interface as sample, conducted experiences after designing simple shapes with topological differences in the aspects of shape adjacency, connectivity, and type of constituent elements.…”
Section: Experiments Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a steady-state key frame selection method for video is proposed by combining curve edge detection and subtitle existence threshold. Unlike the key frame extraction method in the deep learning perspective [ 20 , 22 ], which has the defects of complex feature extraction, difficult algorithm framework and large computational amount [ 7 , 9 , 13 , 21 ], the proposed method adopts the spatio-temporal slice technique in the video feature extraction process to achieve the local operation, which greatly reduces the computational amount. Therefore, the method of this paper is helpful to achieve accurate and fast extraction of the lecture video key frames and it is interesting and worthwhile to research.…”
Section: Introductionmentioning
confidence: 99%